Tandem Interactive Sensing Displays: Tandem Interactive Sensing Display De‐Convoluting Dynamic Pressure and Temperature (Adv. Funct. Mater. 23/2021). (4th June 2021) - Jin, Wookyoung; Kim, Eui Hyuk; Lee, Seokyeong; Yu, Seunggun; Han, Hyowon; Kim, Gwangmook; Lee, Seung Won; Jang, Jihye; Lee, Chang Eun; Shim, Wooyoung; Park, Cheolmin
Abstract : In article number 2010492, Cheolmin Park and co‐workers develop a tandem stimuli‐interactive sensing display, allowing for not only direct visualization of both pressure and temperature but also quantitative de‐convolution of the simultaneously varied stimuli, making the simple but multi‐mode sensing display platform with a tandem architecture suitable for a variety of human interactive and health monitoring systems.